Anti-Mullerian Hormone as A Diagnostic Tool for PCOS Patient : Study in a Tertiary Level Hospital - Afreen, Shabeen; Yasmin, Nilofar; Afreen, Nasreen; Afreen, Tazeen; Rahman, Sumana (Journal of Shaheed Suhrawardy Medical College, 2020)
Polycystic ovary syndrome (PCOS) is a frequently encountered problem affecting 6-11% women of reproductive age.1 Purpose of the study was to determine whether serum AMH level can be used to diagnose PCOS. Methods: It was a cross sectional study conducted among 55 sub-fertile women of reproductive age (18-35 year) in a tertiary level hospital during the period of January 2018 to December 2018. The study subjects were divided into group I (PCOS patient with subfertility by Rotterdam Criteria 2003) and group II (non PCOS subfertile patients of reproductive age). Menstrual history, obstetrical history, physical examination, clinical assessment of androgenesis, ovarian ultrasound assessment and level of AMH, FSH, LH were collected. Result: Twenty five PCOS & 30 non PCOS sub-fertile patients were recruited. Mean age in PCOS & non PCOS were 25.24±4.03 years and 27.8±5.01 years respectively. The mean serum AMH in PCOS was 11.03±3.78 ng/ml and in non PCOS was 3.93±1.92 ng/ml, their difference was statistically significant. Conclusion: AMH can be used as a diagnostic aid for PCOS. J Shaheed Suhrawardy Med Coll, December 2019, Vol.11(2); 142-146